Investigating the utilisation of the micro-functions of Bahasa Melayu by English teachers - Noor Hayati Romli,; Mohd Sallehhudin Abd Aziz,; Pramela Krish, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The controversy over the use of first language (L1) in the second language (L2) classroom has been discussed extensively by numerous scholars in which they either advocate or reject the utilisation of L1 in the target language (TL) classroom. Although the proponents of the monolingual approach argued that there are many disadvantages of utilising the L1, they have yet to present empirical findings to demonstrate that L1 could ultimately hinder the L2 learning. In most L2 classrooms, teachers and students often share similar experiences of L1 utilisation, including in English language classroom in Malaysia. Therefore, it is common for teachers to feel the inclination to use L1 when the other options have failed to explain something during the lessons. A considerable number of local and international studies have pointed out on the wide range of L1 use by L2 teachers. Thus, this study intended to investigate the specific utilisation of micro-functions of L1 (Bahasa Melayu) by English (L2) teachers. A total of 899 English teachers from Pahang were randomly selected to respond to a survey questionnaire which consists of 43 items that represent a myriad functions of Bahasa Melayu (BM). The findings of the study showed that the majority of the respondents utilised a significant number of micro-functions of BM to teach English particularly to assist them in delivering the content of the lessons while its usage was so significant for classroom management and social and interpersonal reasons. The study proposes a need for proper guidelines on how and when teachers should use L1 in L2 teaching.